The Uv-Shielding Property Of Zr0.7ce0.3o2-Kaolinite/Exfoliated Kaolinite Composites Prepared By Differentsynthesis Methods - Nallis, Kry (2013)
Kaolinite was obtained by elutriation of tin slime, which was then exfoliated by planetary ball milling with 40 wt. % of urea for 1, 3 and 5 hours. Then the kaolinite and urea-treated kaolinite samples were characterized by using XRD, XRF, SEM, FTIR, and BET. The characterization results of kaolinite and urea-treated kaolinite samples for 1, 3 and 5 hours proved that kaolinite was successfully exfoliated by urea treatment for 5 hours and the XRD result of kaolinite showed minor gibbsite and muscovite as impurities. Composites of Zr0.7Ce0.3O2-kaolinite/exfoliated kaolinite were prepared by three different in-situ synthesis methods and one solid mixing method. The first in-situ synthesis method was a citric acid complexing method, with and without NH3 added; the second in-situ synthesis method was a soft solution chemical method; and the third in-situ synthesis method was a hydrothermal treatment method with and without sodium oleate added. For the solid mixing method, Zr0.7Ce0.3O2, which was prepared by the three different synthesis methods such as a citric acid complexing method without NH3 added, a soft solution chemical method and a hydrothermal treatment without sodium oleate added, was solid mixed with kaolinite/exfoliated kaolinite using an agate mortar and pestle. The resulting composites were characterized by using XRD, FESEM and UV-Vis.